The Meq Genes of Nigerian Marek’s Disease Virus (MDV) Field Isolates Contain Mutations Common to Both European and US High Virulence Strains - Joseph N. Patria; Luka Jwander; Ifeoma Mbachu; Levi Parcells; Brian Ladman; Jakob Trimpert; Benedikt B. Kaufer; Phaedra Tavlarides-Hontz; Mark S. Parcells (Viruses)
Background: Marek’s disease (MD) is a pathology affecting chickens caused by Marek’s disease virus (MDV), an acute transforming alphaherpesvirus of the genus Mardivirus. MD is characterized by paralysis, immune suppression, and the rapid formation of T-cell (primarily CD4+) lymphomas. Over the last 50 years, losses due to MDV infection have been controlled worldwide through vaccination; however, these live-attenuated vaccines are non-sterilizing and potentially contributed to the virulence evolution of MDV field strains. Mutations common to field strains that can overcome vaccine protection were identified in the C-terminal proline-rich repeats of the oncoprotein Meq (Marek’s EcoRI-Q-encoded protein). These mutations in meq have been found to be distinct to their region of origin, with high virulence strains obtained in Europe differing from those having evolved in the US. The present work reports on meq mutations identified in MDV field strains in Nigeria, arising at farms employing different vaccination practices. Materials and Methods: DNA was isolated from FTA cards obtained at 12 farms affected by increased MD in the Plateau State, Nigeria. These sequences included partial whole genomes as well as targeted sequences of the meq oncogenes from these strains. Several of the meq genes were cloned for expression and their localization ability to interact with the chicken NF-IL3 protein, a putative Meq dimerization partner, were assessed. Results: Sequence analysis of the meq genes from these Nigerian field strains revealed an RB1B-like lineage co-circulating with a European Polen5-like lineage, as well as recombinants harboring a combination of these mutations. In a number of these isolates, Meq mutations accumulated in both N-terminal and C-terminal domains. Discussion: Our data, suggest a direct effect of the vaccine strategy on the selection of Meq mutations. Moreover, we posit the evolution of the next higher level of virulence MDVs, a very virulent plus plus pathotype (vv++).